Innovation and transformation using product lifecycle management enabled by NetWeaver. (1st December 2008) - Gulledge, Thomas; Simon, Georg
Product Lifecycle Management (PLM) is a critical value chain in the US Army's logistics strategy, known as the Single Army Logistics Enterprise (SALE). To enable SALE business processes, the US Army selected the SAP Enterprise Suite. To that end, the SALE vision must be aligned with US Army business processes in order to provide the planning and control mechanisms for successfully deploying such a system. We demonstrate how critical PLM components were designed for organisational innovation and business transformation using SAP NetWeaver technologies. Our main contribution is demonstrating the importance of designing integrated versus best-of-breed solutions when implementing complex solutions.